Combined Application of 17𝛽-Estradiol and Progesterone Enhance Vascular Endothelial Growth Factor and Surfactant Protein Expression in Cultured Embryonic Lung Cells of Mice - Andreas Trotter; Markus Kipp; Roland Matthias Schrader; Cordian Beyer (International Journal of Pediatrics)
Preterm delivery is associated with disruption of the placental supply with 17𝛽-estradiol (E2) and progesterone (P). The aim is to evaluate the role of E2 and P on the regulation of key proteins in lung development in embryonic lung cells. Alveolar cell type II (AT-II) and central lung fibroblast cultures were established from mouse embryos. Cells were exposed for 24 hours to E2 and/or P, the estrogen receptor antagonist ICI 182.780 (ICI) and the progesterone receptor antagonist mifepristone (RU 486). The mRNA expression of vascular endothelial growth factor (VEGF) and surfactant protein B and C (SB-B, SB-C) was determined, and protein levels of VEGF were measured. Only the combined treatment with E2 and P increased mRNA expression and VEGF protein in AT-II cells and lung fibroblasts. Combined treatment also promoted SP-B and SP-C expression in AT-II cells. Pretreatment with ICI and RU 486 completely abolished the E2 and P induced effects. E2 and P enhanced expression of VEGF and surfactant proteins in primary embryonic lung cells and may be involved in regulating expression of key molecules for the prenatal lung development and postnatal lung function.